Postharvest quality and functional compounds in “dedo-de-moça” ‘brs mari’ pepper fruit at different stages of maturity Qualidade pós-colheita e compostos funcionais de pimenta dedo-de-moça ‘BRS Mari’ em diferentes estádios de maturação - Soethe C.* (2016)
© 2016, Universidade Federal de Santa Maria. All rights reserved.The purpose of this study was to evaluate the physicochemical characteristics and functional properties of “dedo-de-moça” ‘BRS Mari’ pepper fruits at different maturity stages, and determine the ideal harvest stage for fresh consumption. The pepper plants were grown in the experimental field of Embrapa Hortaliças (Brasília, DF, Brazil) in 2012, and their fruits were evaluated at 20, 30, 40, 50, 60, 70, and 80 days after anthesis (DAA) to determine the soluble solid content (SS), titratable acidity (TA), SS/TA ratio, color (hue angle and lightness), a, b, and total chlorophyll, total phenolic compounds (TPC), total antioxidant activity (TAA), and capsanthin. It was observed that SS content increased until 70 DAA, and TA increased until 50 DAA, with decrease at 80 DAA. The a and total chlorophyll decreased until 60 DAA. Values for chlorophyll b were high until 30 DAA, and then decreased. The values for hue angle and lightness decreased until 60 DAA, indicating a change from green to red in fruits external color, with small changes in color from 60 to 80 DAA. The TPC content increased until 60 DAA, and then small increases occurred until 80 DAA. The AA increased as the fruit ripened, and the capsanthin content increased until 70 DAA. These results indicated that the ideal stage for harvest of the “dedo-de-moça” ‘BRS Mari’ pepper fruits is at 70 days after anthesis, when they also have a full development of red color in the fruit epidermis.